Exploring the association between BIN1 gene polymorphisms and hippocampal subfield volume in community mild cognitive impairment - Luo, Jiali; Ping, Junjiao; Zhang, Haibo; Zhang, Ying; Tan, Zhenkun; Kong, Chuijia; Liu, Xinxia (Frontiers in Neurology, 2025)
IntroductionMild cognitive impairment (MCI) is an early stage of Alzheimer’s disease (AD), crucial for early diagnosis. BIN1, a key AD susceptibility gene after APOE, has higher brain expression in AD and interacts with tau, affecting its pathology. Specific BIN1 SNPs are linked to AD and MCI, but mechanisms are unclear. This study will explore how BIN1 polymorphisms might influence MCI development and correlate with hippocampal integrity in MCI patients using MRI.MethodsThis study enrolled a total of 52 elderly individuals with MCI and 55 cognitively CN individuals from five communities in Zhongshan Torch Development Zone. Blood samples were collected for analysis of BIN1 rs10200967, rs1060743, and rs4663093 gene polymorphisms, and MRI scans were conducted to assess the volume of hippocampal subregions. The study also seeks to examine the distribution of BIN1 genotypes in both MCI and healthy control populations, as well as to investigate the potential association between BIN1 rs10200967, rs1060743, and rs4663093 genotypes and hippocampal subregion structure in individuals with MCI.ResultsSignificant structural atrophy was observed in multiple hippocampal subregions, including left cornu ammonis (lCA), left dentate gyrus (lDG), left hippocampal-amygdaloid transition area (lHATA), left subiculum (lSubc), right ornu ammonis (rCA), right dentate gyrus (rDG), right subiculum (rSubc), left entire hippocampus complex (lHIP), and right entire hippocampus complex (rHIP) in seniors with MCI compared to those in the CN (p < 0.05), after adjusting for age, gender, education level, and APOEε4 status. Conversely, no significant differences were observed in left entorhinal cortex (lEC), right entorhinal cortex (rEC), right hippocampal-amygdaloid transition area (rHATA), and total intracranial volume (TIV) (p > 0.05). Notably, there were no significant differences in the distribution of BIN1 rs10200967, rs1060743, and rs4663093 genotypes among elderly individuals (p > 0.05). Furthermore, the association between the BIN1 rs10200967 genotype and lHATA atrophy significant in the MCI after adjusting for age, gender, education level, APOEε4 status, and TIV (p < 0.05).ConclusionThis study presents novel findings indicating an association between the BIN1 rs10200967 genotype and lHATA atrophy, with the rs10200967 CC genotype showing a higher volume of lHATA in individuals with MCI. These results suggest that the rs10200967 CC genotype may confer a protective effect against MCI, offering a potential basis for early detection and prevention of AD.